IJIMAI Editor's Note - Vol. 5 Issue 2 - Burgos, Daniel; Nikolov, Roumen; Stracke, Christian M. (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
The International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI) provides an interdisciplinary forum in which scientists and professionals share their research results and report new advances on tools that use AI with interactive multimedia techniques.
Keywords: editors note; IJIMAI